Application of the forum of accumulation of article 5 of Regulation 2016/1103, on matrimonial property regimes, when the divorce proceedings were finalised some time ago. On the judgment of the Provincial Court of Orense of 7 October 2021 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
In this paper we will analyze the forum of accumulation of jurisdiction in Article 5 of Regulation 2016/1103. This text regulates international jurisdiction, the applicable law and the extraterritorial validity of decisions on matrimonial property regime matters. In the aforementioned article, the European legislator includes the accumulation of jurisdiction in matters of matrimonial property regime before the courts of the Member State with jurisdiction in matters of matrimonial crisis, provided that there is a connection between the two matters. In the SAP of Orense, of 7 October 2021, the question arises as to the operability of this forum in cases in which the proceedings on the breakdown of the marital relationship have been concluded for years when the question of matrimonial property regime arises. The court considers that the forum of accumulation can only be used when the matrimonial crisis proceedings are open. There are other authors, on the other hand, who interpret that it could be applied without the need for both proceedings to take place in parallel or concurrently. The conclusions of the paper are agree with the first of the two options mentioned above taking into account the principle of connection between the case and the State with jurisdiction.